The Influence of HPT on Microstructure and Wear Resistance of Al-7wt%Si-2wt%Fe Alloy - Jittraporn Wongsa‐Ngam; Jie Xu; Chakkrist Phongphisutthinan; Terence G. Langdon (Materials science forum, 2021)
An aluminum silicon-based alloy Al-7wt%Si-2wt%Fe, was processed by severe plastic deformation technique in high-pressure torsion (HPT) at room temperature under a pressure of 6.0 GPa and rotational speed of 1.0 rpm with various numbers of turns up to five. Microstructure evolution, especially iron-containing intermetallic phases, was observed using an optical microscope and a scanning electron microscope (SEM). The microstructure results demonstrate that the large strains introduced by HPT at ambient temperature cause fragmentation of iron-intermetallic particles. The degree of fragmentation increases with increasing numbers of turns so that the intermetallic particles decreased in size with increasing imposed strain. In addition, the wear properties were evaluated using ball-on-disc dry sliding testing for both the as-cast material and the alloy processed by HPT using micro-tribometer UMT-2 (CETR Co., USA) following the ASTM G99-05 (2010) standard. The wear tests were conducted on the surface of the samples at 1.5 mm from the disc center under a normal load of 5 N with a rotational speed of 60 rpm and sliding time of 10 min. The friction coefficient and wear volume loss were examined to evaluate the effect of HPT on wear resistance. The results show that the samples processed by HPT have lower average values for the COF and wear volume loss than that of unprocessed samples.
Keywords: Microstructure and mechanical properties; Aluminum Alloys Composites Properties; Metal Alloys Wear and Properties